Assessing the Entrepreneurial Mindset of In-Service Science Teachers in Kogi State, Nigeria - ABIODUN, David Kolawole; DAODU, Joshua Rotimi; ENIOLORUNDA, Olubukola; JAMES, Juliana (Ilorin Journal of Education, 2025)
Entrepreneurship education is vital for Nigeria’s economic growth and innovation. However, the effectiveness of entrepreneurship education in Nigeria is highly dependent on the capacity of teachers to impart entrepreneurial knowledge and skills to their students. Despite the importance of entrepreneurship education, there is dearth of research on the entrepreneurial mindset of in-service science teachers in Nigeria. Teachers’ deficiency in entrepreneurial knowledge and skills hinders students’ entrepreneurial mindset development, affecting Nigeria’s economic growth. This study assessed the Entrepreneurial Mindset of In-service Science Teachers in Kogi State, Nigeria. The study was guided by four objectives and research questions. A descriptive survey research design was employed. The population of the study comprised all in-service science teachers in Kogi State, with a total population of eight hundred and fifty (850). A stratified sampling technique was used to selected 120 in-service science teachers who have a diverse range of backgrounds and experiences in terms of age, gender, educational background, and prior exposure to entrepreneurship, and were used as sample for the study. The instrument used for data collection was structured questionnaire. The instrument was duly validated, pilot tested and the reliability coefficient of the instrument was found to be 0.86. The data obtained from the administration of the instrument were collated and subjected to data analysis using SPSS statistical package version 25.0. The findings revealed that in-service science teachers have moderate levels of entrepreneurial mindset and skills. Furthermore, the study identified key strategies for fostering entrepreneurial mindset development, including mentorship programs, hands-on entrepreneurial projects, professional development work, entrepreneurship courses, training programs, collaboration with industry experts, and entrepreneurial project-based learning. The findings also revealed significant challenges faced by in-service science teachers, including inadequate resources, insufficient training and limited support. The study recommended among others that, entrepreneurship courses or workshops should be organized for in-service science teachers to enhance their understanding of business concepts and innovative thinking.